The small screen : how television equips us to live in the information age - Ott, Brian L.; Wiley InterScience (Online service) (Malden, MA : Blackwell Pub., 2007)
Television is one of the most important socializing forces in contemporary culture. This book is a cultural history of prime-time television in America during the 1990s. Documenting a period when televisions underwent several dramatic changes, this book examines TV as a tool that helped viewers come to terms with the new, fast paced information age.
Cover -- Contents -- Preface -- Chapter 1 Television and Social Change -- The Times They Are a45;Changin8217; -- Television as Public Discourse -- Chapter 2 Life in the Information Age -- The Information Explosion -- Society through the Lens of Technocapitalism -- Social Anxieties in the Information Age -- Chapter 3 Hyperconscious Television -- Embracing 8216;the Future8217;58; The Attitude of Yes -- The Simpsons as Exemplar -- Symbolic Equipments in Hyperconscious TV -- Chapter 4 Nostalgia Television -- Celebrating 8216;the Past8217;58; The Attitude of No -- Dr46; Quinn44; Medicine Woman as Exemplar -- Symbolic Equipments in Nostalgia TV -- Chapter 5 Television and the Future -- 40;Re41;Viewing the Small Screen -- Life and Television in the Twenty45;First Century -- The Next Great Paradigm Shift63; -- References -- Index -- Last Page.
Includes bibliographical references (pages 172-188) and index.
Print version record.
Keywords: Television broadcasting -- Social aspects; SOCIAL SCIENCE -- Media Studies; Television broadcasting -- Social aspects; Electronic books